2000
DOI: 10.1128/mcb.20.7.2446-2454.2000
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interstrand Cross-Links Induce Futile Repair Synthesis in Mammalian Cell Extracts

Abstract: DNA interstrand cross-links are induced by many carcinogens and anticancer drugs. It was previously shown that mammalian DNA excision repair nuclease makes dual incisions 5 to the cross-linked base of a psoralen cross-link, generating a gap of 22 to 28 nucleotides adjacent to the cross-link. We wished to find the fates of the gap and the cross-link in this complex structure under conditions conducive to repair synthesis, using cell extracts from wild-type and cross-linker-sensitive mutant cell lines. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 36 publications
12
121
0
1
Order By: Relevance
“…Instead, DSBs form in S phase when cross-links or perhaps cross-link repair intermediates encounter and stall a replication fork. The mammalian NER factors act on psoralen interstrand cross-links in vitro to produce two incisions, both 5Ј to the cross-link, but leave the cross-link in place (41). Cross-links can be unhooked by the exonuclease activity of XPF-ERCC1 (41), the NER factor homologous to S. cerevisiae Rad1⅐Rad10.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, DSBs form in S phase when cross-links or perhaps cross-link repair intermediates encounter and stall a replication fork. The mammalian NER factors act on psoralen interstrand cross-links in vitro to produce two incisions, both 5Ј to the cross-link, but leave the cross-link in place (41). Cross-links can be unhooked by the exonuclease activity of XPF-ERCC1 (41), the NER factor homologous to S. cerevisiae Rad1⅐Rad10.…”
Section: Discussionmentioning
confidence: 99%
“…The human XPF-ERCC1 complex and the yeast homolog, RAD1-RAD10 complex, contain a 3Ј 5Ј-exonuclease activity (13,22). An ICL-specific 3Ј-incision by the XPF-ERCC1 complex might generate a substrate for its own 3Ј 5Ј-exonuclease activity, which would unhook the ICL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to NER-defective mutants in E. coli and yeast, the NER-defective mammalian cells (except for ERCC-1 and ERCC-4 cells) are only moderately sensitive to DNA cross-linking agents such as mitomycin C (MMC) (8 -11). Moreover, biochemical studies demonstrated that the dual incisions by mammalian NER do not "unhook" ICLs (12,13). Therefore, mammalian cells evidently have a unique mechanism(s) to initiate ICL repair.…”
Section: Dna Interstrand Cross-links (Icls)mentioning
confidence: 99%
“…In yeast and mammalian cells, nucleotide excision repair (NER), recombination, and translesion synthesis, as well as certain mismatch repair proteins, have been reported to participate in ICL repair [2,[5][6][7][8][9][10]. Recombinational repair is in part thought to be a response to formation of double-strand breaks (DSBs) at ICL that appear to be unique to eukaryotes and that arise either as a result of collapsed replication forks blocked at ICL, or as true repair intermediates [8,9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%